Functional Outcome of Closed Reduction and Percutaneous Screw Fixation of Schatzker Type-II Fracture of Tibia - Bhatti, Muhammad Yasir; Shah, Farooq Ahmad; Munawar, Riaz (Indus Journal of Bioscience Research, 2025)
Objective: To examine how close reduction and percutaneous screw fixation (PSF) work to treat Schatzker type-II tibia fractures. Scheme of study: A descriptive case series. Study site and Extent: The current investigation was carried out at Orthopedics Surgery Unit, Ghazi Khan medical college & Allama Iqbal Teaching Hospital Dera Ghazi Khan, Pakistan, during 2023-2024. Materials and Methods: We examined 60 individuals who had Schatzker type-II tibia fractures and were treated with closed reduction and PSF. Each patient was examined at the outpatient clinic. Three months later, patients were assessed using the Rasmussen criteria, and their scores were recorded. If the score was more than 28, the result was considered exceptional. Results: 60 patients were included with mean age of 41.77 ± 11.9 years. Mean Rasmussen score of 60 patients was 20.68 ± 4.721 ranged from 8 to 30. Functional outcome among 5 patients (8.3%) was excellent, among 27 (45%) was good & fair in same number and in only one patient (1.7%) it was poor. Malnutrition, smoking, age, and gender had no influence on functional outcome. Conclusion: Patients treated for Schatzker type II tibia fractures had an excellent functional outcome with closed reduction and PSF.